Responsibilization In Marine Resources Management: A Case Study of Fishery Sector In The Special Region of Yogyakarta, Indonesia - Pranaja, Kevin Arya; Ramdani, Rijal (JURNAL TRIAS POLITIKA, 2025)
Indonesia is one of the world's third-largest fish-producing countries after India and China. In the context of Indonesia, the central government delegates the management of fisheries resources to the provinces or local governments. This study examines what responsibilities the province have and how the province carry out these responsibilities in managing fisheries in their regions. This study uses conceptual framework of responsibilization that focuses on agents, actions, and strategies. Qualitative research is fundamental in this study, where we collected the data through interviews with informants from The Department of Marine and Fisheries (DMF) of Yogyakarta Special Province. DMF of Bantul, DMF of Kulon Progo and DMF of Gunung Kidul and fishermen. We also conducted document analysis particularly from national and provincial regulations as well as strategic planning of marine and fishery development in Yogyakarta province. This study found that the (DMF) of Yogyakarta Special Province manages fisheries resources independently, without delegating responsibilities to the regencies. While tasks related to empowering fishermen and managing fish auction sites are transferred to the regencies along with human resources, the lack of clear responsibility-sharing creates significant challenges. Specifically, the unclear division of responsibilities hampers effective fisheries resource management and results in minimal monitoring by regional departments. Consequently, this lack of oversight allows non-local fishermen to exploit Yogyakarta's marine resources, negatively impacting the welfare of local fishermen. To address these issues, this research recommends revising current regulations to delegate fisheries monitoring responsibilities to the regencies, thereby enhancing resource management and safeguarding local fishermen’s livelihoods.